Laryngeal Dimensions: A Computed Tomography Study - El-Anwar, Mohammad Waheed; Awad, Ali; Hussain, Atef; Hendawy, Ehsan; El Shawadfy, Mohammad A.; Heggy, Mohamed Ibrahim Abdelzeem; Mobasher, Mohamed Adel (International Archives of Otorhinolaryngology, 2025)
The computed tomography (CT) details of the dimensions of the larynx are not fully covered in the literature, so it is important to build up a database for the CT measurements of that area in different ethnic groups. Preoperative details provided by CT are crucial prior to any procedure or approach involving the larynx.To measure and report the different dimensions of the larynx and vocal cords through CT.We analyzed 100 CTs of the larynx (200 vocal cords): axial images were acquired through multiplanar reformation to obtain minute details of all subjects.The mean anteroposterior (AP) vocal fold length (VFL) was of 16.8 ± 2.6 (range: 11.8–22.9) mm, which was significantly longer in male subjects (mean = 18.4 ± 2.2 mm; range = 10.9–19.8 mm) compared to female subjects (mean = 15.3 ± 1.95 mm; range = 10.9–22.9 mm). The mean width of the subglottic area was of 14.88 ± 2.18 (range = 8.9–21.1) mm, which was significantly wider in male subjects (15.6 ± 2.13 mm; range = 9.1–21.1 mm) compared to female subjects (mean = 14.18 ± 1.99 mm; range = 8.9–17.8 mm). There was a positive correlation between the AP and transverse diameters of the subglotic area with the VFL: the longer the AP and transverse diameters of the subglottic area, the longer the VFL and vice versa.The present study improves the awareness of surgeons and radiologists of the laryngeal dimensions, and it can be of help to residents in training.
Keywords: vocal fold; larynx; subglottic; thyroid cartilage; computed tomography